KONGLOMERASI MEDIA DAN DAMPAKNYA PADA PILPRES 2014 - Pembayun, Jaduk Gilang (Interaksi: Jurnal Ilmu Komunikasi, 2015)
AbstractIn this era of globalization, the human’s need to have an fast information becomes veryimportant for the community. The mass media is a form of mass communication that is capable ofproviding the need for quick information about what happened. Facing fierce competition in the massmedia business that requires social and economic strength of this, then there is the tendency of mediaconsolidation which then leads to the emergence of mass media giant group of players who laterled to the concentration of media ownership is often called konglemerasi media. Conglomerationof media influence on the content or programs submitted to the community in which the contentor the program represents the economic and political interests of media owners. As a result, theinterests of the community to get the truth be lost. All this because of the process of agenda setting andframing is done by the media that are tailored to the interests of the owner. Truth is not found in thesecommunities can lead society to accept the truth version from hegemony of mass media.